REKONSTRUKSI SUPERVISI PENDIDIKAN ISLAM: MODEL PROFETIK BERBASIS TASYJIR, TAISIR, DAN ANTI-TA'SIR UNTUK MEWUJUDKAN INDONESIA EMAS 2045 - Amad Chumsoni; Sanusi, Adi; Khairunnisa; Suryadi, Ahmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Indonesia Emas 2045 requires educational supervision that not only improves professional competence but also strengthens teachers' character and spirituality. Contemporary supervision practices in many educational institutions remain largely administrative and compliance-oriented, causing supervision to lose its developmental and humanistic dimensions. This study aims to reconstruct a prophetic model of Islamic educational supervision based on the principles of Tasyjir, Taisir, and Anti-Ta'sir as a conceptual framework for improving educational quality toward Indonesia Emas 2045. The research employs a qualitative approach using library research and content analysis methods. Data were collected from the Qur'an, Hadith, classical Islamic educational literature, and contemporary studies on educational supervision. The findings show that prophetic supervision emphasizes empowerment, facilitation, and humanistic guidance rather than punitive control. Tasyjir functions as a motivational and empowerment mechanism, Taisir provides practical and solution-oriented assistance, while Anti-Ta'sir rejects toxic, rigid, and excessively bureaucratic supervision practices. The study proposes a Prophetic Supervision Framework that integrates Islamic values—tauhid, amanah, ihsan, musyawarah, and adl—with modern transformational supervision approaches. This model contributes theoretically to the development of holistic educational supervision and practically offers guidance for supervisors, principals, and teachers in fostering professional competence, character formation, and spiritual resilience in the digital era.